Interaction between Armed Conflicts and Energy Prices in Colombia - Joaqui-Barandica, Orlando; López-Estrada, Sebastian; Manotas-Duque, Diego F. (International Journal of Energy Economics and Policy, 2025)
This study investigates the complex relationship between armed conflicts and electricity prices in Colombia, considering the effects of climatic variables. Given the strategic importance of energy resources for economic and social development, understanding how conflicts influence energy prices is crucial. Using Generalized Additive Models (GAM) and Distributed Lag Non-linear Models (DLNM), we analyze the immediate and delayed impacts of battles, deaths, solar radiation, and precipitation on electricity prices. Our findings reveal that battles significantly increase electricity prices contemporaneously, highlighting the vulnerability of Colombia’s electrical infrastructure. The DLNM analysis shows that these effects can reemerge weeks after the initial conflict, with significant price increases particularly between weeks four to six and seven to eight. Additionally, climatic variables like solar radiation and precipitation exhibit non-linear effects on electricity prices, where moderate increases in these variables reduce prices, but extreme conditions elevate them. These results underscore the need for integrated strategies that address both socio-political and climatic factors to enhance energy resilience. Our study provides valuable insights for policymakers and energy sector stakeholders, emphasizing the importance of mitigating conflict impacts and adapting to climatic variability to ensure a stable and sustainable electricity supply in Colombia.